Performance Analysis of Different Classifiers to Build A Classification Model and to Improve The Vigilance Skills in Crime Detection Using Data Mining Techniques (International Journal of Advanced Research in Computer Science, 2017)
Data mining is a powerful tool to mine knowledge from large amounts of data. It plays a vital role in the area of which enables fraud detectors who may lack extensive training as data analysts to explore large databases quickly and efficiently. Computer data analysts have started helping the criminal investigators and law enforcement officers to speed up the process of solving crimes by evaluating the crime data and studying the main attributes that lead to further investigation. This paper is an attempt to use the data mining processes particularly to analyse the classifiers and their performance which will help further in enhancing the quality of vigilance department to carry out their task in much faster and efficient way.Keywords: Data mining, Classification, supervised learning